Influence of the Integrated Delivery System on the Medical Serviceability of Primary Hospitals. (3rd August 2021) - Feng, Wenming; Feng, Xin; Shen, Ping; Wang, Zhen; Wang, Bing; Shen, Jiantong; Shen, Xuhui
Abstract : Objective . To explore the change in the medical serviceability of primary hospitals since the establishment of the Huzhou No. 1 People's Hospital medical care group incorporating the integrated delivery system. Methods . With reference to the "Grade Evaluation Standard of General Hospitals in Zhejiang Province" and the "Guidelines for Service Capacity Evaluation of Township Hospitals (2019 Edition), " we analyzed the influence of the integrated delivery system on the capacity of primary medical services and selected the targeted core indicators. From the four dimensions of diagnosis and treatment breadth, diagnosis and treatment efficiency, surgical ability, and patient satisfaction, an index evaluation system was established to explore the changes in the medical serviceability in primary hospitals. Results . The measurements were aimed at four specific issues, that is, the low medical technology level of grassroots personnel, the poor information communication among medical institutions, the difficulty in recruiting people, and the imperfect training mechanism in primary hospitals. After establishing a series of measurements related to the problems faced by the primary healthcare sector in China, the score of breadth of diagnosis and treatment, efficiency of diagnosis and treatment ability, surgical ability, and patient satisfaction of the primary hospitals in our medical group have greatly increased. Conclusion . The integrated delivery system improved the primary hospitals' medical health ability obviously. Our study also provides various useful and operable suggestions for primary healthcare.